Optimasi Perencanaan Keuntungan Produksi pada Pengolahan Rendang di Perusahaan “Rendang Erika” Payakumbuh - Deswani Panggabean; Masrul Djalal; Santosa (Jurnal Optimasi Sistem Industri, 2014)
Rendang is a traditional Minangkabau food. Rendang is generally made of meat, coconut milk and seasoning. Generally rendang semi-wet, but now it has been modified into a dry rendang. Dry rendang widely produced at Payakumbuh, West Sumatra Province. This research was conducted in July to August 2013 at Company " Rendang Erika " Payakumbuh. Research purposes is plotting the maximum profit and optimum production quantities with minimal use of resources. Processing data using the program LINDO (Linear Interactive Discrete Optimizer). The results of the study on the optimum conditions obtained maximum profit of Rp 84,049,360,- per month. The use of herbs and spices and coconut milk have been optimum.